2014
DOI: 10.1177/0284185114559426
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of apparent diffusion coefficient and intravoxel incoherent motion-derived parameters for the characterization of common solid hepatic tumors

Abstract: ADCs showed superior diagnostic performance compared to IVIM-derived parameters in detecting differences between the malignant group and hemangioma group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
2
38
2
Order By: Relevance
“…However, previous studies indicated that ADC could be used as a marker to differentiate disease entities because of its high efficacy and ease of calculation (24)(25)(26)(27). Our results also showed that ADC total slightly exceeded D in terms of maximum AUC values, with higher sensitivity and specificity, but there was no statistical difference between them (P = 0.61), which meant that ADC total and D had the same practical effectiveness.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…However, previous studies indicated that ADC could be used as a marker to differentiate disease entities because of its high efficacy and ease of calculation (24)(25)(26)(27). Our results also showed that ADC total slightly exceeded D in terms of maximum AUC values, with higher sensitivity and specificity, but there was no statistical difference between them (P = 0.61), which meant that ADC total and D had the same practical effectiveness.…”
Section: Discussionmentioning
confidence: 40%
“…A number of studies have pointed out that perfusion parameters between malignancy and benignity are absolutely different because of their microstructure disparities (11,12); however, the nature of these differences in specific lesions is still not completely understood (24)(25)(26). Images captured during routine work in hospitals or from the literature for HCC and FNH show that both of these lesions are characterized by abundant blood supply in the arterial phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…Accumulation of collagen deposits and activated stellate cells contribute to increased hepatic resistance to portal blood flow, development of portal hypertension, and reduced portal blood perfusion. The decrease of blood perfusion can arise from a number of concomitant alterations in the tissue microenvironment, including collagen deposition, fatty (9)(10)(11)15,23,24,42,43,45,46,(48)(49)(50)(51)(53)(54)(55), free-breathing (FB) (19)(20)(21)40,41,47), and breath-hold (BH) (44). Solid line represents the median value of each group.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 99%